Experimental dynamic analysis of the piston assembly of a running single-cylinder diesel engine - Cakir, Mehmet (TAYLOR & FRANCIS LTD, 2021)
In the study, the dynamic analysis of the engine piston assembly was compared with the experimental measurements and the stable working speed was tried to be determined. The theoretical model was developed in addition to the experimental results. The relationships between the forces and torques applied in the crank mechanism, such as gas force and inertial force, are properly addressed. In the stationary conditions, the engine life and vibration should be observed besides the fuel consumption for the efficiency of single-cylinder engines. The result of the analysis shows that the torque value that is low though the vibration is high at low speeds. In high speeds, it was seen that the torque value is more when the vibration is low. This is interpreted that the specific engine should not be operated at low speeds about not vibration. According to the performance analysis, the band between 1600 and 2000rpm seems convenient for ideal engine operation.
Keywords: Piston assembly dynamic analysis; gas torque; indicate torque; engine dynamic; TORQUE ESTIMATION; INDICATED TORQUE; PRESSURE; MODEL; Engineering